2018
DOI: 10.1002/cbdv.201700497
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Product Variability and Biological Activity of the Lactoperoxidase System Depending on Medium Ionic Strength and pH, and on Substrate Relative Concentration

Abstract: The potential of ions produced in water by the lactoperoxidase system against plant pests has shown promising results. We tested the bioactivity of ions produced by the lactoperoxidase oxidation of I and SCN in several buffers or in tap water and characterized the ions produced. In vitro biological activity was tested against Penicillium expansum, the causal agent of mold in fruits, and the major cause of patulin contamination of fruit juices and compotes. In buffers, the ionic concentration was increased 3-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…[9,10]. While studying biological lactoperoxidase activity in the presence of an SCN − /I − mixture, a few articles have addressed the products generated under such and such experimental conditions [11,12,21,27]; several have showed that a more stable oxidative complex was formed in specific pH and ionic strength conditions [25,[27][28][29]. We found OSCN − after LPO oxidation of SCN − and I 2 after LPO oxidation of I − .…”
Section: Influence Of the Substrate Concentrations On Antifungal Actimentioning
confidence: 69%
See 4 more Smart Citations
“…[9,10]. While studying biological lactoperoxidase activity in the presence of an SCN − /I − mixture, a few articles have addressed the products generated under such and such experimental conditions [11,12,21,27]; several have showed that a more stable oxidative complex was formed in specific pH and ionic strength conditions [25,[27][28][29]. We found OSCN − after LPO oxidation of SCN − and I 2 after LPO oxidation of I − .…”
Section: Influence Of the Substrate Concentrations On Antifungal Actimentioning
confidence: 69%
“…SO 4 2− was measured in high concentrations, demonstrating that SCN − was oxidized. 13 C NMR showed that no interhalogen such as ICN, I(SCN) 2 − , or I 2 SCN − was observable [25,38]. Anionic chromatography did not detect OI − .…”
Section: Influence Of the Substrate Concentrations On Antifungal Actimentioning
confidence: 93%
See 3 more Smart Citations